Improving J9 virtual machine with LTTng for efficient and effective tracing. (29th July 2014) - Wang, Yang; Kent, Kenneth B.; Johnson, Graeme; Tse, T. H.; Gotlieb, Arnaud; Chen, Zhenyu
Summary The ability to observe the internal operation of the J9 virtual machine is essential for effective performance tuning. To this end, tracing is an important method, which is the action of recording events from a running system with minimum performance overhead for online or off‐line analysis. In this paper, we propose the integration of LTTng, an effective open‐source tracing toolset, with J9 to improve its tracing functions. With this integration, the tracing component is not only decoupled from the virtual machine but also performed efficiently at both user and kernel levels to achieve a high‐throughput result. To validate the integration and its impact performance, some empirical study results based on SpecJBB2005 and SQLBenchmark (supported by instrumented MariaDB) are also presented. Copyright © 2014 John Wiley & Sons, Ltd.